Gold nanoparticle modified silicon nanowire array based sensor for low-cost, high sensitivity and selectivity detection of mercury ions. (16th March 2020) - Huang, Zonglin; Chen, Shixing; Wang, Yuelin; Li, Tie
Abstract: Heavy metals are the main factor of water pollution which seriously threaten residents and aquatic life. Here, we demonstrated a mercury ion (Hg 2+ ) sensing device based on gold nanoparticles modified silicon nanowire array for highly sensitive, selective and stable detection of mercury ion. Decorated with gold nanoparticles to increase the number of the thiol groups serving as Hg 2+ sensitive probe and improve performance, the silicon nanowire array based sensor had a large response electric signal in detecting low concentration mercury ion. Importantly, the devices exhibits excellent mercury ion sensing attributes in the range of 1 ng/l-10 μ g l −1 with a fairly low detection limit of 0.06 pM. With similar accuracy to ICP-MS, we detected a know sample (1 μ g l −1 ) and unknown sample in less than 1 min. Additionally, the low-cost fabricated process and label free analysis in river water sample make it a potential method in inspecting mercury in water quality.